Leishmania braziliensis exosomes activate human macrophages to produce proinflammatory mediators - Peixoto, Fabio C.; Zanette, Dalila L.; Cardoso, Thiago M.; Nascimento, Mauricio T.; Sanches, Rodrigo C. O.; Aoki, Mateus; Scott, Phillip; Oliveira, Sérgio C.; Carvalho, Edgar M.; Carvalho, Lucas P. (Frontiers in Immunology, 2023)
Exosomes, organelles measuring 30-200nm, are secreted by various cell types. Leishmania exosomes consist of many proteins, including heat shock proteins, annexins, Glycoprotein 63, proteins exerting signaling activity and those containing mRNA and miRNA. Studies have demonstrated that Leishmania donovani exosomes downregulate IFN-γ and inhibit the expression of microbicidal molecules, such as TNF and nitric oxide, thus creating a microenvironment favoring parasite proliferation. Despite lacking immunological memory, data in the literature suggest that, following initial stimulation, mononuclear phagocytes may become “trained” to respond more effectively to subsequent stimuli. Here we characterized the effects of macrophage sensitization using L. braziliensis exosomes prior to infection by the same pathogen. Human macrophages were stimulated with L. braziliensis exosomes and then infected with L. braziliensis. Higher levels of IL-1β and IL-6 were detected in cultures sensitized prior to infection compared to unstimulated infected cells. Moreover, stimulation with L. braziliensis exosomes induced macrophage production of IL-1β, IL-6, IL-10 and TNF. Inhibition of exosome secretion by L. braziliensis prior to macrophage infection reduced cytokine production and produced lower infection rates than untreated infected cells. Exosome stimulation also induced the consumption/regulation of NLRP3 inflammasome components in macrophages, while the blockade of NLRP3 resulted in lower levels of IL-6 and IL-1β. Our results suggest that L. braziliensis exosomes stimulate macrophages, leading to an exacerbated inflammatory state that may be NLRP3-dependent.